2017
DOI: 10.7861/clinmedicine.17-2-161
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis and thrombectomy for acute ischaemic stroke

Abstract: The likelihood of disability-free recovery after acute ischemic stroke is significantly improved by reperfusion either by intravenous thrombolytic drug treatment or with endovascular mechanical thrombectomy in selected cases. The use of intravenous thrombolysis is limited by the short treatment window and you need to assess individual balance of benefit and risk of symptomatic intracranial haemorrhage. Benefit is greater for shorter onset-to-reperfusion time intervals, requiring optimisation of pre-hospital an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…The diagnosis of an acute ischemic infarction, where the damage of brain tissue may still be reversible, enables selection of appropriate treatment and contributes to a more favorable outcome [ 27 ]. Recent studies demonstrated a high efficacy of reperfusion therapies (intravenous thrombolysis and/or thrombectomy) in acute ischemic stroke patients regarding improvement in recovery [ 28 30 ]. Therefore, we focused on stroke patients with middle cerebral artery infarction receiving this gold standard treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of an acute ischemic infarction, where the damage of brain tissue may still be reversible, enables selection of appropriate treatment and contributes to a more favorable outcome [ 27 ]. Recent studies demonstrated a high efficacy of reperfusion therapies (intravenous thrombolysis and/or thrombectomy) in acute ischemic stroke patients regarding improvement in recovery [ 28 30 ]. Therefore, we focused on stroke patients with middle cerebral artery infarction receiving this gold standard treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only 3.4%-5.2% of patients were treated within the short time window. Researchers have been focusing on how to improve the clinical diagnosis and treatment of cerebral infarction beyond the time window of thrombolysis (Feil et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The preferred diagnostic procedure at acute stage involves the acquisition of multi-parametric magnetic resonance imaging (MRI). The possible options for treatment are largely limited to reperfusion therapies known as thrombolysis and thrombectomy, which must be for treatment are largely limited to reperfusion therapies known as thrombolysis and thrombectomy, which must be managed not later than four to six hours after the symptom onset [4]. This treatment is associated with high risk of intracranial hemorrhage.…”
Section: Introductionmentioning
confidence: 99%